Silk protein as a new optically transparent adhesion layer for an ultra-smooth sub-10 nm gold layer. (9th February 2017) - Min, Kyungtaek; Umar, Muhammad; Ryu, Shinyoung; Lee, Soonil; Kim, Sunghwan
Abstract: Ultra-thin and ultra-smooth gold (Au) films are appealing for photonic applications including surface plasmon resonances and transparent contacts. However, poor adhesion at the Au–dielectric interface prohibits the formation of a mechanically stable, ultra-thin, and ultra-smooth Au film. A conventional solution is to use a metallic adhesion layer, such as titanium and chromium, however such layers cause the optical properties of pure Au to deteriorate. Here we report the use of silk protein to enhance the adhesion at the Au–dielectric interface, thus obtaining ultra-smooth sub-10 nm Au films. The Au films that were deposited onto the silk layer exhibited superior surface roughness to those deposited on SiO2, Si, and poly(methyl methacrylate), along with improved adhesion, electrical conductivity, and optical transparency. Additionally, we confirm that a metal–insulator–metal optical resonator can be successfully generated using a silk insulating layer without the use of a metallic adhesion layer.